Weight Loss Experiences of African American, Hispanic, and Non‐Hispanic White Men and Women with Type 2 Diabetes: The Look AHEAD Trial. Issue 8 (24th July 2019) - West, Delia Smith; Dutton, Gareth; Delahanty, Linda M.; Hazuda, Helen P.; Rickman, Amy D.; Knowler, William C.; Vitolins, Mara Z.; Neiberg, Rebecca H.; Peters, Anne; Gee, Molly; Cassidy Begay, Maria; ,
Abstract : Objective: The aim of this study was to characterize weight loss, treatment engagement, and weight control strategies utilized by African American, Hispanic, and non‐Hispanic white participants in the Action for Health in Diabetes (Look AHEAD) Intensive Lifestyle Intervention by racial/ethnic and sex subgroups. Methods: Weight losses at 1, 4, and 8 years among 2, 361 adults with obesity and type 2 diabetes randomized to intervention (31% minority; 42% men) are reported by subgroup. Multivariable models within subgroups examine relative contributions of treatment engagement variables and self‐reported weight control behaviors. Results: All subgroups averaged weight losses ≥ 5% in year 1 but experienced regain; losses ≥ 5% were sustained at year 8 by non‐Hispanic white participants and minority women (but not men). Session attendance was high (≥ 86%) in year 1 and exceeded protocol‐specified minimum levels into year 8. Individual session attendance had stronger associations with weight loss among Hispanic and African American participants than non‐Hispanic white participants at 4 years ( P = 0.04) and 8 years ( P = 0.001). Daily self‐weighing uptake was considerable in all subgroups and was a prominent factor associated with year 1 weight loss among African American men and women. Greater meal replacement use was strongly associated with poorer 1‐year weight losses among African American women. Conclusions: Experiences of minority men and women with diabetes in lifestyle interventions fill important gaps in the literature that can inform treatment delivery.